2022
DOI: 10.3390/ma15238321
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Microstructure of Binary In-Sn Alloys for Flexible Low Temperature Electronic Joints

Abstract: This research evaluates the mechanical properties of a variety of binary In-Sn alloys as potential candidates for low temperature electronic joints. The tensile and hardness tests of as-cast In-5Sn, In-12.5Sn, In-25Sn, In-30Sn, In-35Sn, In-40Sn, In-50Sn, In-60Sn, In-80Sn (wt.%) were assessed at room temperature and compared to those of pure In and Sn. The ultimate tensile strength (UTS) increased from 4.2 MPa to 37.8 MPa with increasing tin content in the alloys under the testing condition of 18 mm/min and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Studies have reported that In-Sn solders had been used for SMT applications, step soldering sequences, heat-sensitive devices, etc. [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that In-Sn solders had been used for SMT applications, step soldering sequences, heat-sensitive devices, etc. [6][7][8].…”
Section: Introductionmentioning
confidence: 99%